DiGeorge syndrome: part of CATCH 22. Issue 10 (October 1993) - Wilson, D I; Burn, J; Scambler, P; Goodship, J
Abstract : DiGeorge syndrome (DGS) comprises thymic hypoplasia, hypocalcaemia, outflow tract defects of the heart, and dysmorphic facies. It results in almost all cases from a deletion within chromosome 22q11. We report the clinical findings in 44 cases. We propose that DiGeorge syndrome should be seen as the severe end of the clinical spectrum embraced by the acronym CATCH 22 syndrome; Cardiac defects, Abnormal facies, Thymic hypoplasia, Cleft palate, and Hypocalcaemia resulting from 22q11 deletions.